Current problems in the energy sector in india and their solutions - Taubaldieva, D. A.; Akmetbekova, G. T. (Journal of Oriental Studies, 2016)
Article is devoted actual problems in the field of power of India. The given problem is actual for the country in the light of world crisis. Power dependence of the country involves a problem of power safety of India. Constantly increasing the country population needs additional power resources. The decision of this question extremely important for national interests and power safety of India. Article considers some alternative sources of power resources of the country.